Let's fill in the blanks step by step to solve the equation:
Given equation: \[ 5x - 12 - 6x = -10x + 7 - 1 \]
Step 1: Combine like terms
On the left side: \[ 5x - 6x = -1x \] So now we have: \[ -1x - 12 = -10x + 6 \]
Response area: \[ -1x - 12 = -10x + 6 \]
Step 2: Get x-terms on the same side of the equation
Let's add \(10x\) to both sides: \[ -1x + 10x - 12 = 6 \] Which simplifies to: \[ 9x - 12 = 6 \]
Response area: \[ 9x - 12 = 6 \]
Step 3: Get constants on the same side of the equation
Now, add \(12\) to both sides: \[ 9x - 12 + 12 = 6 + 12 \] Which simplifies to: \[ 9x = 18 \]
Response area: \[ 9x = 18 \]
Step 4: Get the x by itself by using the inverse operation
Now, divide both sides by \(9\): \[ x = \frac{18}{9} \] Which simplifies to: \[ x = 2 \]
Response area: \[ x = 2 \]
Summary of filled responses:
- Step 1: Response area: \(-1x - 12 = -10x + 6\)
- Step 2: Response area: \(9x - 12 = 6\)
- Step 3: Response area: \(9x = 18\)
- Step 4: Response area: \(x = 2\)
So the answer to the original equation is \(x = 2\).